Factors influencing the critical and creative thinking skills of college students in computational physics courses - Akmam, A; Anshari, R; Jalinus, N; Amran, A (Journal of physics. Conference series, 2019)
Computational thinking that is an essential skill which everyone should learn, especially in Computational Physics courses. Problems in learning Computational Physics courses in the Department of Physics was the ability of students in analyzing problems and designing algorithms for programming is weak, especially since the last 5 years. Therefore, the indication of this condition is the learning outcomes of students in the Computational Physics course that do not reach the mastery learning standard. The capability required to analyze problems and programming design algorithms is the ability to think critically and computionally. This paper will explain the circumstances that influence Critical and Creative Thinking Skills of students in Computational Physics courses. Next, based on the above, we have conducted research that aims to describe the factors that affect students in critical and creative thinking on the subject of Computational Physics. The data were collected using a Likert-scale questionnaire that have 60 statement items. This questionnaire was distributed to 100 college students who have been and are taking a course in Computational Physics. So, the results showed the factors that influence the critical and creative thinking of college students such as the ability to read the book, the time to learn and do the exercises given, learning resources used, students' understanding of the goals of Computational Physics lectures, student interest in Physics courses Computing, the curiosity of the students being taught, the student's enjoyment of the Computational Physics course.